Contagion Effects of the Asian Crisis, Policy Responses and Their Implications - Melanie S. Milo (Philippine Institute for Development Studies (PIDS), 1999)
This paper looks at the contagion effects of the Asian crisis on the Philippine economy, the policy responses, and their social implications. In particular, the paper discusses the role of the financial sector in the evolution of the crisis. In Section II, the recent performance of the Philippine economy, the financial sector and the social sector is reviewed in order to better situate the Asian crisis and its contagion effects on the Philippines. Section III then looks at the economic and social impacts of the Asian crisis on the Philippines, as well as the government's policy responses. The government's social safety net programs are then discussed in Section IV. Finally, Section V presents some conclusions and the continuing policy issues.
Keywords: 330; Asian financial crisis; social safety net programs